Selection and Simulation of Electric Steering Gear Control System - Xin Wang; Jun Yao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
For the electric steering gear control systems, the principle of the system is introduced. Specific model and parameters are selected to deduce the optimal combination of control system and choices method of the steering system model is determined. The transfer function of motor according to the parameters is achieved and simulation results are gained based on MATLAB. Simulation results show that this method can meet the performance requirements of electric steering gear, the control method is simple and easy to work to achieve. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2643